2004
DOI: 10.1021/bi048428o
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Analysis of the Binding of DNA-Bending Proteins HMGB1, NHP6A, and HU Reveals Their Ability To Form Highly Stable DNA−Protein Complexes

Abstract: The mechanical response generated by binding of the nonspecific DNA-bending proteins HMGB1, NHP6A, and HU to single tethered 48.5 kb λ-DNA molecules is investigated using DNA micromanipulation. As protein concentration is increased, the force needed to extend the DNA molecule increases, due to its compaction by protein-generated bending. Most significantly, we find that for each of HMGB1, NHP6A, and HU there is a well-defined protein concentration, not far above the binding threshold, above which the proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
183
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(215 citation statements)
references
References 39 publications
31
183
0
1
Order By: Relevance
“…However, the data are consistent with a chromosome composed of highly condensed DNA. This description gives a segment length of order 40 nm, which is more in line with studies of DNA bound to nucleoid-associated proteins (35)(36)(37)(38). A recent study of the positioning of chromosomal loci in E. coli similarly concluded that the chromosome contains a higher-order structure that can be modeled as a condensed DNA fiber (5).…”
Section: Discussionsupporting
confidence: 57%
“…However, the data are consistent with a chromosome composed of highly condensed DNA. This description gives a segment length of order 40 nm, which is more in line with studies of DNA bound to nucleoid-associated proteins (35)(36)(37)(38). A recent study of the positioning of chromosomal loci in E. coli similarly concluded that the chromosome contains a higher-order structure that can be modeled as a condensed DNA fiber (5).…”
Section: Discussionsupporting
confidence: 57%
“…All single-molecule micromanipulation experiments were performed by using the magnetic tweezers setup described (23,24). Flow-cell preparation, force measurements, and calibration were performed as described (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…Controlled forces were applied to the bead by using permanent magnets (Smith et al, 1992;Strick et al, 1996Strick et al, , 1998Strick et al, , 2000, and bead positions were measured using digital videomicroscopy and bead-tracking computer software. We used two setups: in the first "vertical MT," the bead is pulled perpendicular to the focal plane, so DNA extension is determined by autofocusing software ( Figure 2a); details are described in Skoko et al (2004). In the second "transverse MT" system the DNA is extended in the focal plane ( Figure 2b); for details, see Yan et al (2004).…”
Section: Magnetic Tweezer (Mt) Setups Allow Precise Observation and Cmentioning
confidence: 99%